Impulsivity, online disinhibition, and risk taking among digital millennials: challenges of E-safety in industry 4.0 - Erfianti, Levina Gendis; Mohd Mahudin, Nor Diana (2018)
Digital millennials (i.e., people born from 1980 through 2004) have been often portrayed as being ready to embrace emerging technologies. The envisioned future of Industry 4.0 entails the blending of hardware, software, and people to complete work and given their affinity for technologies, the Millennials could be regarded as a much-needed asset in this future workforce. However, systematic research on how this group understand and react to the safety issues surrounding the use of technologies has been lacking. In particular, behaviours such as impulsivity, online disinhibition, and risk-taking among them remain unclear. This study investigated these gaps with a sample of 203 Millennials of various nationalities groups of university students. Using the short version of the Urgency, Premeditation, Perseverance, Sensation Seeking, and Positive Urgency (S-UPPS) scale, the Online Disinhibition Scale (ODS), and the Online Risky Behavior (ORB) scale, the results indicated that each of the impulsivity and online disinhibition subscales showed various level of significance against online risky behaviour subscales. These findings implied that the Millennials’ tendency to engage in risky behaviour varied across individuals. The study’s findings are also discussed in relation to the key challenges associated with e-safety in the future trends toward the gig economy, crowd-working, and Industry 4.0.